Corporate Criminal Liability In Environmental Pollution Crimes - T. Riza Zarzani; Ismaidar Ismaidar; Mula Sihombing (International Journal of Sociology and Law, 2024)
Corporate crime against the environment is a major crime and is very dangerous for human life. Even though there are laws that regulate forms of legal sanctions for corporations, in fact environmental pollution still occurs. In environmental criminal cases involving corporations, the principle of absolute responsibility should be applied, so that the application of absolute responsibility can be expanded. This means that the sanctions that will be imposed on the perpetrators are not only civil compensation claims but also criminal legal protection. Legal sanctions for corporations proven to have committed criminal acts of environmental pollution include imprisonment, fines and additional penalties. Law Number 32 of 2009 concerning Environmental Protection and Management states that the criminal act referred to is committed by or on behalf of a legal entity, company, association, foundation or organization, the threat of a criminal fine is increased by one third. The method used in this research is normative legal, namely research that refers to legal norms contained in statutory regulations, literature, legal norms that exist in society and the data obtained. The type of research used is qualitative research which is carried out by examining literature materials in the field of law and legislation relating to legal policies for corporations that commit criminal acts of environmental pollution. This research aims to determine criminal liability for corporations that are proven to have committed environmental pollution and to determine the factors inhibiting criminal liability for corporations that have committed environmental pollution.